Sea salt as a potential ocean mirror material1. Issue 49 (30th May 2015) - Rowland, T.; Hailes, H. C.; Evans, J. R. G.
<x xml:space="preserve">Abstract</x> The additives used to produce ocean foams also inhibit Ostwald ripening of seasalt producing very fine particle size and a reflectance of 77% so that seasalt can make a contribution to surface albedo.